Genetic Transformability of Selected Kenyan Groundnut (Arachis hypogaea L.) Genotypes with IPT Gene Using Cotyledonary Node Explants - Purity G. Limbua; Mathew P. Ngugi; Richard O. Oduor (Advances in Agriculture)
Groundnut (Arachis hypogaea L.) is an important crop in terms of income and nutrition. Despite its importance, groundnut yield is limited by environmental factors such as drought. This work reports the genetic transformability of Kenyan groundnut (Arachis hypogaea L.) genotypes with isopentenyl transferase (IPT) gene towards drought tolerance. The cotyledonary nodes of six Kenyan adapted groundnuts genotypes (ICGV 12991, CG 7, Red Valencia, ICGV 90704, Chalimbana, and JL 24) were transformed using Agrobacterium tumefaciens strain EHA 101 carrying PNOV-IPT binary vector containing an IPT gene, which was driven by SARK promoter and terminated by TNOS terminator. The vector also contained the phosphomannose isomerase (PMI) gene for the selection of transformed tissues. Putative transformants were tested for the presence of the transgene by PCR designed to amplify the IPT gene sequence. Gene expression was confirmed by RT-PCR. Transformation frequency was calculated as a percentage of the number of putative transformants divided by the total number of infected cotyledonary nodes. This ranged from 9.87% for ICGV 90704 to 19.77% for JL 24. Transformation efficiency was calculated as a percentage of the number of PCR positive plants divided by the total number of cotyledonary nodes infected. This ranged from 0% for ICGV 12991 and Chalimbana to 1.74% for JL 24. The data suggest the possibility of transforming groundnuts with the IPT gene and regenerating normal transgenic plants. This information will be useful during the transformation of groundnut towards different factors that affect production.